2019
DOI: 10.1016/j.exer.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of topical anti-fibrotics on corneal nerve regeneration in vivo

Abstract: Recent work in vitro has shown that fibroblasts and myofibroblasts have opposing effects on neurite outgrowth by peripheral sensory neurons. Here, we tested a prediction from this work that dampening the fibrotic response in the early phases of corneal wound healing in vivo could enhance reinnervation after a large, deep corneal injury such as that induced by photorefractive keratectomy (PRK). Since topical steroids and Mitomycin C (MMC) are often used clinically for mitigating corneal inflammation and scarrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 85 publications
0
20
0
Order By: Relevance
“…The increased expression of TGF-β1 after injury plays positive roles by regulating the immune response, modulating neuronal phenotype and regulating expression of growth factors important for neuronal repair [12][13][14]. However, TGF-β1 also stimulates the formation of fibrotic scars at the lesion site; this can be problematic for nerve regeneration, as scar-forming cells can inhibit regrowth, plasticity and recovery of damaged neurons [15][16][17][18]. Scar formation is particularly detrimental in the cornea, where it decreases transparency and the ability to see.…”
Section: Introductionmentioning
confidence: 99%
“…The increased expression of TGF-β1 after injury plays positive roles by regulating the immune response, modulating neuronal phenotype and regulating expression of growth factors important for neuronal repair [12][13][14]. However, TGF-β1 also stimulates the formation of fibrotic scars at the lesion site; this can be problematic for nerve regeneration, as scar-forming cells can inhibit regrowth, plasticity and recovery of damaged neurons [15][16][17][18]. Scar formation is particularly detrimental in the cornea, where it decreases transparency and the ability to see.…”
Section: Introductionmentioning
confidence: 99%
“…However, only SP-8356 depleted α-SMA (+) myofibroblast population in injured cornea whereas PA slightly decreased the number of myofibroblasts and α-SMA expression ( Figure 2). Similarly, Hindman et al and Kim et al [38,39] reported that PA decreased the number of myofibroblast in damaged cornea, but this reducing effect disappeared when PA treatment is discontinued. In addition, Hill et al [40] reported that corticosteroid is ineffective to eliminate myofibroblast population in damaged cornea.…”
Section: Discussionmentioning
confidence: 85%
“…Presently, topical corticosteroids are frequently used to prevent corneal haze in clinical fields and PA is one popular topical steroid [5,[35][36][37][38]. Thus, we used PA as a positive control drug.…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of TGF-β1 after injury plays positive roles by regulating the immune response, modulating neuronal phenotype and regulating expression of growth factors important for neuronal repair [12-14]. However, TGF-β1 also stimulates the formation of fibrotic scars at the lesion site; this can be problematic for nerve regeneration, as scar-forming cells can inhibit regrowth, plasticity and recovery of damaged neurons [15-18]. Scar formation is particularly detrimental in the cornea, where it decreases transparency and the ability to see.…”
Section: Introductionmentioning
confidence: 99%
“…Although corneal nerves are part of the peripheral nervous system and able to regenerate, wounding of the cornea often results in abnormal reinnervation, with surprisingly serious and long-lasting effects [23-30]. We recently showed that corneal myofibroblasts, which differentiate largely from stromal keratocytes in and around the wound site [31], inhibit the regrowth of corneal nerves into the wound area [16, 18]. Importantly, this effect was reproduced in vitro : when corneal myofibroblasts were co-cultured with neurons derived from the ND7/23 cell line, they inhibited neurite outgrowth [16].…”
Section: Introductionmentioning
confidence: 99%